APLIKASI CASE BASED REASONING UNTUK RESEP MINUMAN TRADISIONAL JAWA (Information Technology and Telematics, 2014)
AbstractWith Each area has a different kind of traditional drink one area in Indonesia that has many kinds of traditional beverage is the island of Java , in Java there are many types of beverages ranging from traditional beverage that serves as herbs or drinks are usually consumed daily , with many types of traditional drink in the Java lot of people who will be curious to try to make it , but many do not know what materials are needed and how the steps to make the traditional drink . This research is the application of Case -Based Reasoning ( CBR ) based mobile web , with the aim of facilitating the user in finding traditional Javanese drink recipes .There are 4 stages in the process of Case Based Reasoning method ( CBR ) ie retrieve , reuse , revise , retain . Retrieving process is where the system looks for similarities between the input materials with traditional Javanese drink recipe  ingredients . To retrieve the process will be weighted using the nearest neighbor method nearest neighbor.metode This is a method to find the value of materials , reuse is the process of searching for the highest similarity value of traditional Javanesebeverages that will be used as a solution . In the process of revise the system will store data in the database material . Retain the process used when a solution has been found by experts and will save it back to the database .Keywords:Javanese Traditional Recipes, Case BasedReasoning, Nearest Neighbor.